Multiple vaginal stones secondary to an ectopic ureter in an adult female patient: a case report (Medical Journal of Indonesia, 2022)
Vaginal stone is a rare case with low incidence. Ectopic ureter insertion into the vagina is one of the congenital abnormalities that may lead to vaginal stone formation. True incontinence persisting until adulthood might indicate an ectopic ureter, often associated with a complete duplex renal system. We reported an adult female that came with a chief complaint of true incontinence since she was young. However, it was left untreated due to limited healthcare facilities in her area and low socioeconomic status. The computed tomography examination revealed a right complete duplex renal system, with upper moiety inserted into the vagina, and multiple vaginal stones. Thus, stone removal and ureteroneocystostomy procedure were performed. No further complaints or complications were recorded after the hospital discharge.